Digitalization in Indonesian Culinary Human Resource Management: Strengthening Identity and Competitiveness - Suprihandari, Miya Dewi (Universitas Muhammadiyah Surabaya, 2025)
Digitalization has become a key factor in the transformation of human resource (HR) management, including in the Indonesian culinary sector. This study aims to analyze how the application of digital technology in HR management can strengthen cultural identity and increase competitiveness in the global market. Using a qualitative approach and case studies, this study found that digitalization, such as the use of technology-based training applications and online recruitment platforms, can improve operational efficiency while preserving the traditional values ​​of Indonesian cuisine. Digital technology is not only an operational tool, but also a transformational strategy that allows local culinary companies to maintain cultural heritage while competing in the global market (Westerman et al., 2014). These findings provide new insights into the importance of integrating digitalization in the cultural sector as a strategic step to face the challenges of the globalization era.